Effects of induced alkalosis on simulated match performance in elite female water polo players - Tan, F.; Polglaze, T.; Cox, G. R.; Dawson, B.; Mujika, I.; Clark, S. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
This study investigated the effects of sodium bicarbonate (NaHCO3) ingestion on simulated water polo match performance. Twelve elite players from the Australian National Women`s Water Polo Squad (age 23.7 ± 3.0yr, height 1.73 ± 0.05 m, body mass 75.7± 8.0 kg) participated in the study. In a randomized cross-over double-blind design, players ingested 0.3 g/kg of NaHCO3 or placebo 90 min before performing a 59-min match-simulation test (MST) that included 56 × 10-m maximal-sprint swims as the performance measure.Capillary blood samples were obtained preingestion, pre- and post-warm-up, and after each quarter of the MST. Preexercise ingestion of NaHCO3 was effective in enhancing extracellular pH from baseline levels of 7.41; ±0.01 (M; ±90% confidence limits) to 7.49; ±0.01 and bicarbonate levels from 24.4; ±0.3 to 28.5; ±0.5 mmol/L. The percentage difference in mean sprint times between trials showed no substantial effects of NaHCO3 (0.4;±1.0, effect size = 0.09; ±0.23; p = .51). These findings are contrary to those of previous NaHCO3 studies on simulated team-sport performance, but this investigation is unique in that it examined highly trained athletes performing sport-specific tasks. In conclusion, water polo players should not expect substantial enhancement in intermittent-sprint performance from NaHCO3 supplementation.